Plasma C-Terminal Agrin Fragment as an Early Biomarker for Sarcopenia: Results From the GenoFit Study. (16th May 2021) - Pratt, Jedd; De Vito, Giuseppe; Narici, Marco; Segurado, Ricardo; Pessanha, Ludmilla; Dolan, Jackie; Conroy, Judith; Boreham, Colin
Abstract: Barriers associated with direct muscle quantification have prevented a consistent implementation of therapeutic measures for sarcopenia. Recently, the relevance of circulating C-terminal agrin fragment (CAF) as an accessible screening method alternative for sarcopenia has gained credence. Accordingly, this study aimed to verify the pertinence of plasma CAF as a biomarker for sarcopenia. Three hundred healthy adults aged between 50 and 83 years took part in this study. Sarcopenia was diagnosed according to the European Working Group on Sarcopenia in Older People criteria. Body composition was assessed using dual-energy x-ray absorptiometry, while muscle strength was examined using hand dynamometry. Plasma CAF concentrations were determined using a commercially available ELISA kit. CAF concentrations were significantly associated with appendicular lean mass (ALM), but not grip strength ( p = .028, p = .575, respectively). Plasma CAF concentrations were significantly elevated in sarcopenic individuals compared to nonsarcopenic ( p < .001). Overall, individuals with low grip strength or low ALM displayed significantly higher CAF levels compared to healthy controls, after adjusting for age and body mass index ( p = .027, p = .003, respectively). In males, those with low grip strength or low ALM had significantly elevated CAF levels ( p = .039, p = .027, respectively), while in females, only those with low ALM had significantly raised CAF concentrations, compared to healthy controls ( p = .035). Our findings illuminate the potential relevance of CAF as an accessible biomarker for skeletal muscle health. CAF determination may enhance clinical practice by facilitating more widespread treatment strategies for sarcopenia. Nevertheless, future research is needed to confirm the diagnostic pertinence of CAF concentrations in screening for sarcopenia.